Spatial distribution of Pratylenchus brachyurus in a soybean area of eastern Maranhao, Brazil - Brito Freitas, Jose Roberto; Teixeira, Daniel De Bortoli; Moitinho, Mara Regina; Silva Junior, Joao Fernandes da; Siqueira, Diego Silva [UNESP]; Figueiredo Barbosa, Bruno Flavio [UNESP]; Martins Soares, Pedro Luiz [UNESP]; Pereira, Gener Tadeu [UNESP] (Univ Federal Rural Pernambuco, 2019)
The root-lesion nematode, Pratylenchus brachyurus, is native to the Brazilian Cerrado region. Although soybean is not a natural host of this nematode, its advance on Cerrado areas has made this species become an important pathogen for the crop. This study aimed to assess the spatial distribution of P. brachyurus and its influence on soybean crop productivity in eastern Maranhao. For this, a sampling was conducted in 142 georeferenced points distributed in an area of 180 x 180 m. Plant and soil samples were collected, being the nematodes extracted and counted. Spatial patterns were estimated using geostatistical analysis. Anisotropic exponential models were adjusted for all studied variables with higher ranges in the direction of soil tillage and planting (135 degrees). The increase in nematode population, as well as its spatial pattern, was related to the presence of roots of the host plant in the soil. The direction of soil tillage and planting influenced the distribution of nematodes in the area, being the main controlling factor of their spatial patterns.
Keywords: anisotropy; geostatistics; nematodes